Resveratrol enhances A1 and hinders A2A adenosine receptors signaling in both HeLa and SH-SY5Y cells: Potential mechanism of its antitumoral action - Muñoz-López, Sonia; Sánchez-Melgar, Alejandro; Martín, Mairena; Albasanz, José Luis (Frontiers in Endocrinology, 2022)
Despite great efforts, effective treatment against cancer has not yet been found. However, natural compounds such as the polyphenol resveratrol have emerged as promising preventive agent in cancer therapy. The mode of action of resveratrol is still poorly understood, but it can modulate many signaling pathways related to the initiation and progression of cancer. Adenosinergic signaling may be involved in the antitumoral action of resveratrol since resveratrol binds to the orthosteric binding site of adenosine A2A receptors and acts as a non-selective agonist for adenosine receptors. In the present study, we measured the impact of resveratrol treatment on different adenosinergic pathway components (i.e. adenosine receptors levels, 5’-nucleotidase, adenosine deaminase, and adenylyl cyclase activities, protein kinase A levels, intracellular adenosine and other related metabolites levels) and cell viability and proliferation in HeLa and SH-SY5Y cell lines. Results revealed changes leading to turning off cAMP signaling such as decreased levels of A2A receptors and reduced adenylyl cyclase activation, increased levels of A1 receptors and increased adenylyl cyclase inhibition, and lower levels of PKA. All these changes could contribute to the antitumoral action of resveratrol. Interestingly, these effects were almost identical in HeLa and SH-SY5Y cells suggesting that resveratrol enhances A1 and hinders A2A adenosine receptors signaling as part of a potential mechanism of antitumoral action.